Vibration acoustic modulation for bolt looseness monitoring based on frequency-swept excitation and bispectrum - Zhao, Nan; Linsheng, Huo; Song, Gangbing (Smart materials and structures, 2023)
The monitoring of bolt looseness is crucial to ensure the safety and reliability of structures. Prior studies have demonstrated that the vibro-acoustic modulation (VAM) method based on the nonlinear ultrasonic theory is sensitive to the early looseness of bolted connections. However, one limitation of the traditional VAM method is that the low frequency (LF) and high frequency (HF) for excitation should be specified in advance. The resonant frequency of the bolted structures changes after loosening, leading to inaccuracies in monitoring results if pre-specified excitation frequencies are used and not adapted to the new situation. To address this limitation, this paper improves the VAM method by using swept sine signals for both LF and HF excitations and relying on the bispectrum energy of the measured response to indicate the bolt pre-load. A steel bolted connection was fabricated and loaded on a universal testing machine to simulate different bolt pre-loads. Three low-cost lead zirconate titanate patches served as the LF actuator, HF actuator and sensor in the experiment. The experimental results demonstrate that the improved VAM method can evaluate the bolt looseness with better efficiency and robustness than the traditional VAM methods which use fixed frequencies as excitations. Therefore, the proposed method in this paper can potentially monitor the damages in complex structures based on nonlinear ultrasound theory.